2010
DOI: 10.1093/hmg/ddp588
|View full text |Cite
|
Sign up to set email alerts
|

Pkd1 transgenic mice: adult model of polycystic kidney disease with extrarenal and renal phenotypes

Abstract: While high levels of Pkd1 expression are detected in tissues of patients with autosomal dominant polycystic kidney disease (ADPKD), it is unclear whether enhanced expression could be a pathogenetic mechanism for this systemic disorder. Three transgenic mouse lines were generated from a Pkd1-BAC modified by introducing a silent tag via homologous recombination to target a sustained wild-type genomic Pkd1 expression within the native tissue and temporal regulation. These mice specifically overexpressed the Pkd1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 53 publications
5
62
0
4
Order By: Relevance
“…Strikingly, renal analysis in both the Pkd1TAG and SBPkd1TAG mouse models revealed upregulation of c-Myc mRNA expression and protein that is markedly enhanced in the cystic epithelia (104). Pkd1 dysregulation in these mice promotes cellular responses typical of full-length c-Myc.…”
Section: Orthologous Pkd Mouse Models Co-associate With C-myc Overexpmentioning
confidence: 97%
See 1 more Smart Citation
“…Strikingly, renal analysis in both the Pkd1TAG and SBPkd1TAG mouse models revealed upregulation of c-Myc mRNA expression and protein that is markedly enhanced in the cystic epithelia (104). Pkd1 dysregulation in these mice promotes cellular responses typical of full-length c-Myc.…”
Section: Orthologous Pkd Mouse Models Co-associate With C-myc Overexpmentioning
confidence: 97%
“…Two orthologous dosage-increased Pkd1 mouse models, including one with extrarenal manifestations, reproduce all of the typical PKD characteristics including fibrosis and inflammation (103,104) (Figure 1). Strikingly, renal analysis in both the Pkd1TAG and SBPkd1TAG mouse models revealed upregulation of c-Myc mRNA expression and protein that is markedly enhanced in the cystic epithelia (104).…”
Section: Orthologous Pkd Mouse Models Co-associate With C-myc Overexpmentioning
confidence: 99%
“…[20][21][22] Two-fold or higher expression of Pkd1 causes kidney cysts in mice. 23,24 Knockdown of Pkd1 disrupts tubulogenesis in 3D culture. 25 In this study, we found that overexpression of Pkd1 is also sufficient to disrupt tubulogenesis.…”
mentioning
confidence: 99%
“…Chez la souris, la mutation des gènes Pkd1 et Pkd2 conduit à des malformations des valves cardiaques [38], ainsi qu'à des défauts de cloisonnement des chambres cardiaques [38,39]. Dans le cas d'une perte de fonction, un myocarde plus fin a été observé [11,38], alors que la surexpression de Pkd1 (entraînant un niveau 2 à 15 fois supérieur au niveau normal) conduit à un effet inverse d'hypertrophie du myocarde [40], ce qui rappelle la maladie humaine. Lorsque la mutation de Pkd1 est restreinte aux cellules endothéliales [41] ou aux muscles lisses et cardiaque [42], elle ne cause pas de défaut cardiaque, à la différence de la mutation ubiquitaire.…”
Section: Polycystinesunclassified